Real analysis - Royden, Halsey L.; Fitzpatrick, Patrick M. (Uttar Pradesh Pearson, 2023)
Royden's Real Analysis has contributed to educating generations of mathematical analysis students. The 5th Edition of this classic text presents some important updates while presenting measure theory integration theory and elements of metric topological Hilbert and Banach spaces. An undergraduate course on the fundamental concepts of analysis is assumed.
Keywords: Theory and elements; Fundamental concepts of analysis; Generations of mathematical analysis